Billy the squid - Dowland, Collin; Firmin, Peter (Great Britan Barrington Stoke, 2001)
Do you like adventure stories? This one takes place under the sea. Something very fishy is going on down there. Can anyone save the town from the claws of a monster? If you have a wacky sense of humour, dive into this book!